A cross‐level model of shared leadership, meaning, and individual creativity. (20th December 2020) - Liang, Bingqian; van Knippenberg, Daan; Gu, Qinxuan
Summary: Research on leadership and creativity is dominated by the study of leadership from people in formal leadership positions. The very nature of creativity requires self‐direction, however. This points to shared leadership, a process in which members dynamically share the leadership role, as a particularly relevant influence to consider. Drawing on psychological empowerment theory, we develop the shared leadership perspective on individual creativity. We argue that shared leadership has a cross‐level influence on individual creativity that is mediated by the experience of meaning of work and moderated by individual differences in power distance value: for individuals lower on power distance, shared leadership has a positive linear relationship with individual creativity; for individuals higher on power distance, shared leadership has a curvilinear relationship with individual creativity that is decreasingly positive. Using a sample of 623 members from 95 teams in 34 Chinese organizations, we find support for this multilevel model. Findings offer theoretical implications for shared leadership and creativity research and provide managerial implications.